Mesin Melipat Pakaian Automatik - Mohamed Nor, Mohd Faizal; Md Armaludin, Inshyrah Harlina Alyea Laila; Kamarozaman, Nur Atiqah Adilah; Ahmad Ridauddin, Shafiah Aienn (Multidisciplinary Applied Research and Innovation, 2023)
The purpose of this project is to design a portable Automatic Clothes Folding Machine by using servo motor, Arduino UNO and several other components as the main requirement to move the folding board for folding clothes. The use of these components is to replace manpower to perform the daily routine. This is because it has caused problems such as lack of time to fold clothes if folding clothes manually. Therefore, the implementation of this project has been done to achieve one of the objectives of this project which is to study the concept and method of folding clothes quickly and easily using folding aids. Literature study is also used in this project as reference data in producing this Automatic Clothes Folding Machine. With the existence of this Automatic Clothes Folding Machine will also ease the human burden to perform daily routines. Through the implementation of this project, the Automatic Clothes Folding Machine has been designed with a medium size and light weight according to the comfort of the user and easy to move. The implementation of this project also focuses on those who are mothers or housewives or employees in laundry shops. Therefore, the process to produce this machine has been done neatly and thoroughly through several tests to obtain the best results.